Studi Filogenetik Kantung Semar (Nepenthes spp.) Berdasarkan Sekuens Gen Nep2 dan trnK di Paparan Sunda: Studi in Silico (Program of Biology Education, Universitas Lambung Mangkurat, 2023)
The pitcher plant (Nepenthes spp.) has the highest species diversity in Sunda Shelf. This study aims to analyze the phylogenetic profile of Nepenthes spp. in Sunda Shelf based on Nep2 and trnK gene sequences. This research was conducted by in silico, downloaded from the Genbank website. The sequences consisted of 21 species for the Nep2 gene sequence and 29 species for the trnK gene sequence. The Nepenthes species used in this study were Nepenthes of Sunda Shelf including Sumatera and Kalimantan as in group also Nepenthes of Sulawesi and Papua as out group. The downloaded sequences were then analyzed for their genetic distance using p-distance method. The phylogenetic tree was constructed using Maximum Likelihood analysis on MEGAX software. The results of the phylogenetic tree analysis based on Nep2 gene sequences showed that there were 2 main clades, clade I which consisted of 19 Nepenthes species of Kalimantan, Sumatera, and Sulawesi and clade II which consisted of two species, namely N. Tobaica (Sumatera) and N. Papuana (Papua). The phylogenetic tree analysis based on the trnK gene showed that there were 2 main clades, clade I consisting of 26 Nepenthes species of Kalimantan, Sumatera, Sulawesi, and Papua and clade II consisting of N. hamata (Sulawesi), N. muluensis and N. murudensis (Kalimantan). A Total of 26 species in clade I have a genetic distance between 0.05%-2.17%, while the 3 species in clade II have a genetic distance between 8.27%-10.02%. Differences in genetic distance and the formation of clades in the phylogenetic tree are predicted to be due to the geological history of the formation of islands originating from the Sunda Shelf and Sahul Shelf.